Predicting Pulmonary Arterial Hypertension in Patients with Connective Tissue Disease: A Systematic Review of Risk Factors and Screening Strategies - Yeni Oktasari; Yessica Fianita (International Medical Journal Corp. Ltd, 2026)
Introduction: Pulmonary arterial hypertension (PAH) is a severe and life-threatening complication of connective tissue diseases (CTD), associated with significant morbidity and mortality. Early detection through effective screening strategies and identification of robust risk factors is crucial for improving patient outcomes. This systematic review aims to synthesize and evaluate the current evidence on risk factors, predictors, and screening strategies for PAH in patients with CTD. Methods: A systematic literature search was conducted to identify studies investigating risk factors, biomarkers, screening strategies, and predictive models for PAH in CTD patients. Studies were included if they enrolled patients with systemic sclerosis (SSc), systemic lupus erythematosus (SLE), mixed connective tissue disease (MCTD), or other CTDs, and reported quantitative measures of association or screening performance. Data were extracted on CTD populations, PAH definitions, risk factors, screening modalities, and predictive performance metrics. Results: Fifty-four studies met inclusion criteria, encompassing prospective and retrospective cohorts, systematic reviews, and meta-analyses. The majority focused on SSc (n=38), followed by SLE (n=8) and MCTD (n=1). Composite screening algorithms (DETECT and ASIG) demonstrated superior performance (sensitivity 94-100%, NPV 87-100%) compared to single modalities. Echocardiography showed moderate sensitivity (49-95%) with threshold-dependent specificity (43-100%). NT-proBNP exhibited pooled sensitivity of 67% (95% CI 52-79%) and specificity of 84% (95% CI 75-91%). In SSc, key risk factors included low DLCO (45-70% predicted), anti-centromere antibodies, telangiectasias, and nailfold capillaropathy (OR 7.3, 95% CI 3.0-18.0). In SLE, anti-RNP antibody (OR 3.68, 95% CI 2.04-6.63), antiphospholipid antibodies (OR 2.28, 95% CI 1.65-3.15), Raynaud's phenomenon (RR 1.83, 95% CI 1.41-2.37), and interstitial lung disease (RR 4.36, 95% CI 2.42-7.85) were significant predictors. Survival was worse in SSc-PAH (67% at 3 years) compared to SLE-PAH (87% at 3 years). Screening programs improved survival outcomes compared to clinical diagnosis. Discussion: This systematic review demonstrates that multi-modal screening algorithms significantly outperform single-modality approaches for CTD-PAH detection. Risk factor profiles differ substantially between CTD subtypes, reflecting distinct underlying pathophysiological mechanisms. The predominance of SSc-focused evidence highlights a critical research gap for non-scleroderma CTDs. The integration of emerging modalities including exercise testing, nailfold capillaroscopy, and genetic risk scores may further refine risk stratification. Conclusion: Current evidence supports annual multi-modal screening in SSc patients using composite algorithms incorporating echocardiography, pulmonary function tests, and biomarkers. For SLE and other CTDs, targeted screening based on identified risk factor profiles is recommended. Future research should focus on validating prediction models in diverse CTD populations and investigating early intervention strategies in high-risk patients.